Pengaruh Self Assesment System, Tarif Pajak Dan Modernisasi Sistem Administrasi Perpajakan Terhadap Tax Evasion” (Studi Kasus Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Pratama Tigaraksa Kabupaten Tangerang) - Aan Nurlistiani; Rudy (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine whether there is an influence between the selfassessment system, tax rates, and modernization of the tax administration system on tax evesion among individual taxpayers registered at the Tigaraksa Partama Tax Service Office. The population in this study is individual taxpayers registered at the Tigaraksa Pratama Tax Service Office. The sample used in the study was obtained from calculations using the Slovin formula where from a population of 736,107, 100 research data samples were obtained. The data used in this study is primary data by distributing questionnaires to taxpayers. The results of this study obtained simultaneously Self-assessment system, tax rates, and modernization of the tax administration system affect tax evasion. Tax rates and modernization of the tax administration system partially affect tax evasion. Meanwhile, the Selfassessment system does not affect tax evasion.